Pengetahuan dokter gigi mengenai pencabutan gigi pada pasien terapi bisfosfonat - Jonathan Gavriel; Anggraeny Putri Sekar Palupi (Jurnal Kedokteran Gigi Terpadu, 2023)
Background: Appropriate dental extraction management with osteoporosis patient that consume bisphosphonate is the best way to prevent bisphosphonate related osteonecrosis of the jaw Objective: evaluate the dentist knowledge and awareness in West Jakarta about dental extraction management in patient with osteoporosis that consume bisphosphonate Methods: This research method is a descriptive observational study with a cross-sectional design with 97 respondents. The data was collected through a questionnaire addressed to West Jakarta-based dentists, and the data was then displayed in the form of a graphic and percentage. The data obtained was then categorized into 3 level which are high if the respondents have ≥80 score, average if the respondents have 60-70 score and low if the respondents have score ≤50 Result: there are 85,54% respondents with a low level of knowledge, 10,31% who have average level of knowledge and 5,15% who have low level of knowledge. Conclusion: Dentists level of knowledge in West Jakarta about dental extraction with osteoporosis patients under bisphosphonate treatment is categorized low.